Role of Greenland Sea Gyre Circulation on Atlantic Water Temperature Variability in the Fram Strait - Sourav Chatterjee; Roshin P. Raj; L. Bertino; Ø. Skagseth; M. Ravichandran; Ola M. Johannessen (Geophysical Research Letters)
Abstract Atlantic Water (AW) transported from the Nordic Seas is the major source of oceanic heat to the Arctic Ocean. Based on results from the TOPAZ reanalysis, a regional coupled ice‐ocean data assimilation system, we show that interannual variability of AW temperature in the Fram Strait (FS) is associated with the strength of the Greenland Sea gyre (GSG) circulation. The response of the GSG to the anomalous wind stress curl over the Nordic Seas modifies the AW inflow and thus influences the variability of AW temperature in the FS. A stronger (weaker) GSG circulation increases (decreases) the AW flow speed toward FS, leading to increased (decreased) oceanic heat content and higher (lower) AW temperature therein. This implies that the Nordic Seas circulation is not only a passive conduit of AW, but its response to overlying atmospheric variability can also largely influence the AW temperature in the FS by modifying the transport of AW.